((The impact of strategic Orientation in the performance of banks private sector Iraqi / compared to the entrance.)) - صيهود علي موات; شونه حسام حمدان (Journal of Economics and Administrative Sciences, 2017)
bjective researcher through this research to Put a theoretical framework to strategic orientation the center on the market in the business and the diagnosis and interpretation of the nature of the link between relationships and influencing strategic orientation dimensions Almtmthelh organizations (Entrepreneurial Orientation, market Orientation, Interaction Orientation) and the performance of the Iraqi Private Banks The research community and the level of dimensional and through the use of scale (Balanced Scorecard) Bmnzawradtha the four, the test of this research in the Iraqi banking sector (Gulf Commercial Bank and the Bank of Ashur International), and applied research on a sample of (85)Director and employee distributors in several administrative levels (manager, department manager, branch manager, higher management staff), and use the search resolution tool to collect data and information as well as personal interviews Program and some private banks annual reports, has sought research to test a number of major and minor hypotheses concerning Relations link and relationships influence between research variables, in order to answer questions related to the problem of research and questions basic (Are Iraqi banks Private research community has a strategic orientation led to achieve better performance?, What is the effect of strategic orientation of the three dimensions (Entrepreneurial Orientation, market Orientation, Interaction Orientation) the performance of the Iraqi private banks?). and the dimensions of the strategic orientation its effects on the performance of banks varying sample of the research it is found that the impact of the Entrepreneurial Orientation trend in the first priority, Interaction approach in the second priority, market orientation in the third priority. There are also showing high positive correlation between the strategic orientation(In general) and the performance of the banking banks the same topic, also showed the results of descriptive analysis (general rate) to keep strategic orientation of Gulf Commercial Bank and the Bank of UNESCO’s International achieved a force that builds high paragraphs Find variables implying the absorption of researched banks of the importance of strategic orientation dimensions are all "which will reflect positively its performance. strategic direction because of its direct impact on the performance of banks and the success of its business, , as well as in-depth studies to find out the reasons for the negative impact of the move towards the market in the performance of banks researched and processed increases the efficiency of its interaction with other.